Ethnographical anti-Semitism (the special aspect of the holocaust atmosphere in the south-eastern Moravia in the period of 1938 to 1945) - Mezihorák, František (Civilia, 2016)
The fates of the Jewish population in the south-eastern Moravia, which we shall call Slovácko (regarding the aspect indicated in this article's caption), were enacted following the scenario valid for all the region of the Czech countries: based on the racist policy they are Slovakia deprived of their rights and human dignity, then they are centralized in transports, deported into concentration camps and exterminated. Into such horrifying scheme, just the specific regional figures could be introduced. And yet, there is something about the south-eastern Moravia, that is special and repulsively quaint - it is the misuse of ethnography in order to support tendencies and proceeding leading to holocaust.
Keywords: Jewish; anti-Semitism; Ethnography; Moravia; Slovácko; World War II; Great Slovakia; Joža Uprka